Outcomes of Calycanthus L. Introduction into the Conditions of Volyn Upland and Possibilities of Its Usage in the Greenery Planting - Gavrylyuk, Olga (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
The paper presents results of researching of the bioecological features of three Calycanthus L. species, introduced into the conditions of the Volyn Upland. It is proved that the rhythm of seasonal development of the studied species in the conditions of introduction is stable, regardless of the temperature fluctuations the plant bloom and fruit annually. It has been proved, that under the conditions of introduction the plants have passed a complete cycle of growth and development, which is evidence of their adaptation to the regional conditions. The study of the ability of introduced species to seed and vegetative reproduction showed that first one is more promising. The success of introduction and their future usage in greenery plantings have been evaluated. These plants are characterized by high and average adaptation – IV–II and high and satisfactory acclimatization – 68–91 points. According to the assessment of their viability, it should be noted that the first group of perspective should include species of Calycanthus fertilis Walter, which plants have a higher score of the winter resistance. Ecological plasticity is a key factor of introduction success for North America plant species under introduction into the conditions of the Volyn Upland. North-American woody plants can be widely used not only at the locations of natural growing, but also in conditions of introduction. The evaluation of prospects of these species has a great significance for their wide distribution and introduction into the culture. Based on our observations, all species of Calycanthus L. deserve attention and a score of 4 was obtained on the decorative scale.